'Soft' usability problems with consumer electronics: the interaction between user characteristics and usability. (1st January 2012) - Kim, Chajoong; Christiaans, Henri
The paper reports a study into consumers' 'soft' usability problems they experience using electronic household products. These problems cannot be traced back to a specification violation failure, classified as no failure found (NFF). The aim of this study is to find a relationship between consumers' soft usability problems and their personal characteristics, encompassing demographical and cognitive aspects. The complaints collected through an exploratory survey were classified into three categories of soft usability problems. The findings indicate that demographic, socioeconomic and cultural characteristics as well as personal traits show significant correlations with these problem categories. Based on the data preliminary user profiles were made. By providing a new definition of usability problems and by user profiling, this study is expected to help design teams to get a better understanding of their target group. The implications of these findings for the product development process are discussed.